Profiling the Impact of Tinnitus in Indian Population Using International Classification of Functioning Classification System: A Cross-Sectional Study - Prashanth Prabhu; Ardra Kannancheeri; Sajana Aryal; Kavassery Venkateswaran Kavassery Nisha (Auditory and Vestibular Research)
Background and Aim: Tinnitus is a complex, multifactorial condition involving auditory and non-auditory systems. Individuals with bothersome tinnitus often report various associated problems, reflecting its diverse impact. This study aimed to evaluate the overall effect of tinnitus and correlate these findings with standard auditory measures using the International Classification of Functioning, disability, and health (ICF) framework. Methods: The study included 117 individuals with tinnitus (mean age=39.7 years, SD=12.58; 52.1% female). Participants completed the Tinnitus Handicap Inventory (THI). Hyperacusis and misophonia were assessed using the Khalfa hyperacusis questionnaire and the Amsterdam misophonia scale-revised. Retrospective data on pure-tone audiometry and speech identification scores were collected. Two open-ended questions —the problem effects question and the life effects question —were used to explore the impact of tinnitus on daily functioning and quality of life. Results: A total of 221 responses were collected for the problem effects question and 140 for the life effects question. Results showed that affected domains differed between the two questions: activity limitation was most prominent in the problem effects responses, while body function was most affected in the life effects responses. Conclusion: No significant correlations were found between ICF-based responses and auditory measures like pure-tone audiometry or speech identification scores. However, strong correlations were observed between the problem effects, life effects, and THI scores, emphasizing the importance of self-reported measures in understanding the impact of tinnitus.